2009
DOI: 10.1586/egh.09.21
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Crohn’s disease: prevention and treatment

Abstract: Crohn's disease is a chronic, relapsing-remitting inflammatory disease of the intestinal tract that commonly requires surgical treatment. Unfortunately, the majority of patients will ultimately develop postoperative disease recurrence and require subsequent surgery. A number of medications have been researched for the maintenance of postoperative remission. Of these, few have demonstrated consistent efficacy. A recently published randomized, controlled trial indicated that infliximab is effective in the mainte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Although WCE is safe and tolerable for patients, the risk of capsule retention in patients with small-bowel strictures is a major concern [9]. In addition, efforts have been made to establish a specific scoring system for WCE to assess small-bowel CD [25].…”
Section: Wireless Capsule Endoscopymentioning
confidence: 99%
See 2 more Smart Citations
“…Although WCE is safe and tolerable for patients, the risk of capsule retention in patients with small-bowel strictures is a major concern [9]. In addition, efforts have been made to establish a specific scoring system for WCE to assess small-bowel CD [25].…”
Section: Wireless Capsule Endoscopymentioning
confidence: 99%
“…However, there is no optimal algorithm to be validated for the management and prevention of postoperative CD. A tailored therapy based on a patient's risk profile of postoperative recurrence has been proposed by the majority of experts [8][9][10][11][12][13]. Patients with high risk of recurrence should be treated with anti-TNF agents immediately after surgery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, at least one third of CD patients develop potentially life threatening intestinal strictures, with resulting obstructions that often necessitate surgical intervention. Despite the frequency of these stenotic strictures in CD, there are few therapeutic options, with longterm anti-inflammatory therapy often proving ineffective in preventing fibrosis (for reviews see [116][117][118]). Although stricturoplasty has shown some positive results (for review see [119], it generally provides only short-term resolution, with repeated procedures required.…”
Section: Intestinal Fibrosis: a Maladaptive Host Responsementioning
confidence: 99%
“…Several medications have been studied, with variable results. Despite treatment with 5-aminosalicylates, steroids, antibiotics, and immunomodulators, 1-year endoscopic recurrence rates are as high as 60% [4]. Recent, small, postoperative anti-tumor necrosis factor-a (TNF-a) prevention studies have shown promise in preventing Crohn's disease recurrence after surgery [5][6][7].…”
Section: Introductionmentioning
confidence: 99%